Poetic Images of Nightingale in the Art Song. On Some Aspects of Musical Meaning - Żerańska-Kominek, Sławomira (Interdisciplinary Studies in Musicology, 2019)
Birds are not only part of nature, but also an important element of culture. The life and behaviour of some bird species has been reflected in literary tradition in the form of poetic images and representations reflecting existential problems and stereotypically associated with specific states of the human psyche. These images and their poetics inspired composers of the Romantic era to create their musical, semantically charged counterparts. A special place in European poetry and music is occupied by the nightingale, which has wide symbolic connotations. My article discusses the musical replicas of the nightingale’s poetic representations in the songs of F. Liszt, J. Brahms, F. Schubert and K. Szymanowski. Each of the presented songs constructs meaning and relates to the poetic images in a different manner, despite the suggested or even expected repeatable nature of the emotional expression and experience symbolically associated with this bird.